Imminent Entry and the Transition to Multimarket Rivalry in a Laboratory Setting - Charles F. Mason; Owen R. Phillips (Center for Economic Studies and ifo Institute (CESifo), 2016)
In this paper we study the behavior of rivals when there is a known probability of imminent entry. Experimental markets are used to collect data on pre- and post-entry production when there is an announced time of possible entry; some markets experience entry and other do not. In all pre-entry markets competition is more intense. Post-entry behavior in all markets is more competitive compared to a baseline that had no threat. There is evidence that post-entry multimarket contact raises outputs in those markets that did not experience entry, behavior we generally refer to as a conduit effect.
Keywords: L10; L40; C90; 330; entry; rivalry; market experiments